POLYPHARMACY AND RISK OF INTOXICATION: ANALYSIS OF THE USE OF PSYCHOTROPIC DRUGS POLIFARMACIA Y RIESGO DE INTOXICACIÓN: ANÁLISIS DEL USO DE PSICOFÁRMACOS - Normando, Lara Vasconcelos (2024)
Introduction: Every day the number of people who need treatment with psychotropic drugs due to mental health problems grows. Thus, an increase in the number of medications per individual is evidenced, causing psychotropic polypharmacy. There are several benefits, however, there are several risks. Among them, the risk of intoxication stands out. Thus, inquiring about the polypharmacy of psychotropic drugs and the risk of intoxication, the study was carried out. Objective: to analyze through the current literature the risk of intoxication derived from psychotropic polypharmacy. Method: systematic literature review, through a search in the Latin American and Caribbean Health Sciences, Google Scholar and Scientific Electronic Library Online databases, using the descriptors: Polypharmacy; Psychotropics; Intoxication; Poisoning. Through this, six articles were selected that made up the inclusion and exclusion criteria of the present study. Result: The studies list that psychotropic polypharmacy is common, however, combinations without scientific evidence, prescription without dialogue with other professionals and inappropriate, can cause several risks. Thus, the risk of intoxication in patients with polypharmacy is great and can have catastrophic effects on the individual's   health, even leading to death. Conclusion: It is evident that the dissemination of knowledge to the population about polypharmacy and the risk of intoxication, in addition to improving communication between professionals, observation of the patient in a holistic and integral way and dissemination of knowledge with evidence is essential to minimize wrong combinations, incorrect prescriptions, unnecessary polypharmacy and the risks to patients of intoxication and other consequences.